1999
DOI: 10.1103/physrevlett.83.5202
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Superradiant Scattering of Laser Light from Bose-Einstein Condensates

Abstract: In a recent MIT experiment, a new form of superradiant Rayleigh scattering was observed in Bose-Einstein condensates. We present a detailed theory of this phenomena in which condensate depeletion leads to mode competition, which, together with the directional dependence of the scattering rate, is ultimately responsible for the observed phenomena. The nonlinear response of the system is shown to be highly sensitive to initial quantum fluctuations which cause large run to run variations in the observed superradi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
235
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(243 citation statements)
references
References 17 publications
(23 reference statements)
8
235
0
Order By: Relevance
“…However, in view of an experimental observation of entanglement, a detailed analysis of the sources of noise is in order, which in turn may be a serious limitation for entanglement in CARL [11]. Also, it has not yet been proved that BEC superradiance experiments may generate entangled atom-photon states, as suggested in [9]. This issue is investigated for the first time in this paper, where we demonstrate the entangled properties of the atom-atom and atom-photon pairs produced in the linear stage of the superradiant CARL regime in a BEC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in view of an experimental observation of entanglement, a detailed analysis of the sources of noise is in order, which in turn may be a serious limitation for entanglement in CARL [11]. Also, it has not yet been proved that BEC superradiance experiments may generate entangled atom-photon states, as suggested in [9]. This issue is investigated for the first time in this paper, where we demonstrate the entangled properties of the atom-atom and atom-photon pairs produced in the linear stage of the superradiant CARL regime in a BEC.…”
Section: Introductionmentioning
confidence: 99%
“…without the optical cavity. In this case the radiation is emitted along the 'end-fire modes' of the condensate [9] with very large radiation losses (in the mean field model, with κ ≈ c/L, where κ is the cavity decay rate and L is the condensate length). In a recent work [5] it has been shown that atom-atom and atom-photon entanglement can be produced in the linear regime of CARL, in which the ground state of the condensate remains approximately undepleted.…”
Section: Introductionmentioning
confidence: 99%
“…As long as depletion of the condensate is not large, i.e. N 0 (0)−N 0 (t) < 0.1N 0 (0), this number is given by N kSR0 (t) = exp(G kSR0 N 0 t) − 1 [15]. At later times, when N kSR0 ∼ 10 >> 1 typically obtained for t > 10µs for V 0 < 5E r ,f † kSR0 can be neglected in Eq.…”
mentioning
confidence: 99%
“…The SRB gain is related to G kSR0 the gain for the SR0 process by the relation [15], with L and W the length and width of the Bose gas after its loading inside the optical lattice. In the superfluid phase, the Bose gas conserves its aspect ratio [10] as long as the radial confinement by the lattice laser remains negligible so that this relationship between superradiance gains is assumed to be independent on the lattice depth.…”
mentioning
confidence: 99%
See 1 more Smart Citation